Hybrid Method between the Discrete Wavelets Translate Technique and the Chaos System Based by the Least Significant Bit Algorithm to Encrypt and Hide a Digital Video File - Hasan Ahmed (Al-Rafidain Journal of Computer Sciences and Mathematics)
The use of computers today is the most important and widespread means of storing, retrieving and circulating information through local and international networks and smart phones. Thus it is possible to intercept information through different networks or access to computers, whether independent or connected with the network for the purpose of viewing its contents or stealing information or to tamper with, and in this light must ensure the protection, reliability and credibility of information and preservation of the emergence of various means of protection such as the use of encryption and techniques of hiding or coverage of information. This research is based on a hybrid method between the Discrete Wavelets Translate technique (DWT) and the Chaos system based on the Least Significant Bit algorithm (LSB) to encrypt and hide a digital video file within another digital video that represents the cover by inserting the digital video file and segmenting it into a set of frames and then analyze each frame to its colors (red, green and blue) and then study the color values ​​of each frame and the process of encryption based on the equation of the logistics function (chaotic functions), and the application of the Discrete Wavelets Translate technique on the color slides of the cover frame. The hiding process is done using the Least Significant Bit algorithm based on the logistic function by calculating the series of random locations of cover area. The results showed that the hybridization of the Discrete Wavelets Translate technique and the chaos system based on the Least Significant Bit algorithm was an effective method for encrypting and hiding digital video files. After applying the work algorithms to a set of samples, the results showed consistency and compatibility in the encrypting and hiding process with the samples that was dealt with.